OBTAINING PHOTOGRAMMETRIC DATA BY USING NON-PROFESSIONAL UAVS - Darchuk, Kostiantyn; Sukhyj, Petro; Kostaschuk, Ivan (REVIEW OF INTERNATIONAL GEOGRAPHICAL EDUCATION, 2021)
This article covers the features of using non-professional UAVs to obtain photogrammetric information. The analysis of scientific articles on the use of UAVs in research was carried out. The algorithm of photogrammetric works was made, and also the task for aerial photography in the mobile software product DroneDeployv.4.1.0 was formed. Aerial photography was performed under the most favorable conditions using a UAV DJI Mavic 2 Zoom from an altitude of 70 meters and with a spatial resolution of 0.12 m. Reference ground points were created, the coordinates of which were determined using GNSS observations in RTK and static modes. The problematic aspects of aerial photography using non-professional UAVs are highlighted. Post-processing of aerial photography results in the software product AgisoftPhotoScanv.1.4 was made. A number of spatial models were formed: point clouds, 3-D surface, orthophoto plan, elevation map, etc. By comparing them with terrestrial geodetic surveys in the GIS package ArcGISv.10.5, the accuracy of the obtained materials was determined, which was 0.35 m in plan and 0.52 in height.
ОТРИМАННЯ ФОТОГРАММЕТРИЧНИХ ДАНИХ ЗА ДОПОМОГОЮ НЕПРОФЕСІЙНИХ БПЛА
Keywords: UAVs; aircraft; cartography; orthophotoimaging; digital; GNSS survey; photogrammetric processing; aerialphotography; 3-D modeling; gis-mapping